Modeling-Based Group Counseling to Enhance Career Planning in Eleventh-Grade Students - Fitri Annisa, Dona; Eluemuno, Azukaego Ifeoma; Kumar, Ashok (Journal of Counseling and Educational Research, 2025)
This study aims to examine the effectiveness of a group guidance approach using modeling techniques in enhancing career planning among high school students. Given the rapidly evolving job market and rising youth unemployment, structured career planning interventions for high schoolers are urgently needed to prevent future career misalignment and underemployment. The research employed a mixed-method design with an explanatory sequential approach, involving 36 eleventh-grade science students at SMAN 1 Purwakarta. Participants were selected via purposive sampling, targeting eleventh-grade science students with intermediate career-planning readiness to ensure intervention relevance. Quantitative data were collected through a career planning questionnaire, while qualitative data were obtained from interviews and observations. A 20-item Likert-scale career planning questionnaire measured four dimensions: decision-making, understanding, information-seeking, and self-efficacy (α=0.87), administered pre- and post-intervention.  The results indicate a significant improvement in career planning scores, with the average increasing from 100.36 (pretest) to 114.39 (posttest) (p = 0.000). The decision-making aspect showed the highest increase (+4.83), followed by career understanding (+4.62) and career information-seeking (+4.58). The findings demonstrate that modeling techniques using inspirational videos and interactions with real-life models such as professionals and alumni successfully visualized concrete steps in career planning, enhanced self-efficacy, and reduced student confusion. Qualitative findings confirm that group dynamics facilitated experience-sharing and enriched students' perspectives on the professional world. This study concludes that the approach is effective in helping students develop structured and comprehensive career planning. Practical implications emphasize the importance of integrating modeling-based career guidance programs into school counseling curricula, supported by external collaborations and the use of digital media.